Ethical leadership and school effectiveness: The mediating roles of affective commitment and job satisfaction - AYŞE NEGİŞ IŞIK (International Journal of Educational Leadership and Management, 2020)
This study examines how ethical leadership influences school effectiveness via the mediating role of affective commitment and job satisfaction. For this purpose, 306 teachers completed measures of ethical leadership, affective commitment, job satisfaction, and school effectiveness. The results supported the hypothesized positive links of ethical leadership to affective commitment, job satisfaction, and school effectiveness. The results also revealed that work attitudes (i.e., affective commitment and job satisfaction) partially mediated the relationship between ethical leadership and school effectiveness, indicating both direct and indirect effects of ethical leadership on school effectiveness. In light of these findings, a number of recommendations were given for further research, specifically regarding school administrative research and applications.